2019
DOI: 10.1111/pim.12621
|View full text |Cite
|
Sign up to set email alerts
|

The Nrf2 pathway is required for intracellular replication ofToxoplasma gondiiin activated macrophages

Abstract: Summary Reactive oxygen species (ROS) produced by oxidases and nonenzymatic sources are important for host defence against intracellular pathogens. In this study, we knocked out the Nrf2 gene in RAW264.7 cells using the CRISPR/Cas9 system and investigated the antioxidant effects of the Nrf2 pathway in the cells stimulated by IFN‐γ and TNF‐α. The results indicated that the Nrf2 signalling pathway is necessary for maintaining redox homeostasis in activated RAW264.7 cells. Inactivation of Nrf2 impaired parasite g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The capacity of ES to reduce LPS -induced inflammation when lacking Nrf2 was impaired, suggesting that anti-inflammatory role of ES may be primarily involved in the Nrf2 pathway. It has been also reported that T. gondii can balance the oxidative stress of IFN-γ and TNF-α –stimulated macropahges ( 40 ). In addition, we not only showed that Nrf2 participated in the development of T. spiralis ES -induced M2, but also verified that Nrf2 KO macrophage induced by T. spiralis ES failed to attenuate the severity of colitis and produced lower levels of IL-10 in vivo , suggesting that Nrf2 KO macrophages treated by ES did not exert their anti-inflammatory effects on colitis.…”
Section: Discussionmentioning
confidence: 98%
“…The capacity of ES to reduce LPS -induced inflammation when lacking Nrf2 was impaired, suggesting that anti-inflammatory role of ES may be primarily involved in the Nrf2 pathway. It has been also reported that T. gondii can balance the oxidative stress of IFN-γ and TNF-α –stimulated macropahges ( 40 ). In addition, we not only showed that Nrf2 participated in the development of T. spiralis ES -induced M2, but also verified that Nrf2 KO macrophage induced by T. spiralis ES failed to attenuate the severity of colitis and produced lower levels of IL-10 in vivo , suggesting that Nrf2 KO macrophages treated by ES did not exert their anti-inflammatory effects on colitis.…”
Section: Discussionmentioning
confidence: 98%
“…Nrf2-mediated anti-inflammatory response is thought to be ROS-dependent, although a recent report showed a direct inhibitory effect of Nrf2 on the recruitment of RNA polymerase II, preventing the transcription of genes coding for the proinflammatory cytokines IL-1β, IL-6 [9,10]. Furthermore, activation of Nrf2 signaling pathway in phagocytic cells improved their anti-viral and anti-bacterial functions [11][12][13]. Based on the literature, we selected 4 pharmacological compounds, found to modulate Nrf2 signaling, with anti-inflammatory properties: sulforaphane (SFN), wogonin (WG), oltipraz (OTZ), and dimethyl fumarate (DMF) [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The authors demonstrated that activation occurs in a p62-dependent manner. Activation of NRF2 was shown to be crucial for parasite growth [55]. Moreover, infection with Leishmania was also shown to activate the NRF2 pathway as NRF2-deficient cells were shown to exhibit decreased parasite load [56].…”
mentioning
confidence: 99%